2015
DOI: 10.3945/ajcn.114.099184
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prepregnancy waist circumference and BMI in relation to gestational weight gain and breastfeeding behavior: the CARDIA study

Abstract: Maternal prepregnancy body size was differently associated with GWG and breastfeeding behavior depending on the location of the fat mass. Thus, maternal fat distribution may be a more important determinant of GWG and breastfeeding behavior than BMI alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
0
12
1
Order By: Relevance
“…However, there’s not an official GWG recommendation based on Chinese BMI cut-off points for Chinese women. 18.3% of women in our study had central adiposity prior to pregnancy, which is lower than the previously reported percentage (25.7%) in developed countries [24]. In general, the status of pre-pregnancy weight and waist circumference in our cohort was less than ideal.…”
Section: Discussioncontrasting
confidence: 88%
“…However, there’s not an official GWG recommendation based on Chinese BMI cut-off points for Chinese women. 18.3% of women in our study had central adiposity prior to pregnancy, which is lower than the previously reported percentage (25.7%) in developed countries [24]. In general, the status of pre-pregnancy weight and waist circumference in our cohort was less than ideal.…”
Section: Discussioncontrasting
confidence: 88%
“…Together with the standard obesity measure of body mass index (BMI), another important measure for maternal obesity is gestational weight gain (GWG) (Ferraro et al 2015). Excessive gestational weight gain is an established predictor of pregnancy and post-pregnancy complications, as well as postpartum weight retention, which is known to influence the future risk of obesity (Gunderson 2009; Kirkegaard et al 2015; Krukowski et al 2016). Several studies have demonstrated that risks associated with excessive GWG are higher in early pregnancy, suggesting that early GWG may be an important and clinically relevant time period with respect to adverse health outcomes (Fontaine et al 2012; Ferraro et al 2015; Hedderson et al 2010; Hedderson et al 2014; Carreno et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a considerable body of research has demonstrated that greater pre-pregnancy maternal BMI is associated with reduced initiation rates and shorter breastfeeding duration (Rasmussen, 2007). Kirkegaard et al (2015) found that the pre-pregnancy BMI strongly contributed to breastfeeding cessation within 6 weeks of breastfeeding initiation. Hatsu, McDougald, and Anderson (2008) found, somewhat paradoxically, that women at 12 weeks postpartum who were exclusively breastfeeding consumed more calories but also lost more body weight than mothers who non-exclusively breastfed, although the differences were not statistically significant ( p = .08 and p = .07, respectively).…”
Section: Call Outmentioning
confidence: 95%